Fracture Risk in Men With Congestive Heart Failure : Risk Reduction With Spironolactone - CARBONE, Laura D; CROSS, Jessica D; DISHMON, Dwight A; NESHEIWAT, Joseph P; HAJJAR, Mohammad A; CHISHTI, Waqas A; NASSER, Wael; KHAN, Mehwish; WOMACK, Catherine R; CHO, Tara; HASKIN, Ashley R; WEBER, Karl T; et al. (Journal of the American College of Cardiology, 2008)
The purpose of this study was to determine whether spironolactone use is associated with fractures in men with congestive heart failure (CHF). In rats with aldosteronism, spironolactone preserves skeletal strength. However, in humans, the relationship of spironolactone to fractures is not known. The medical records of all male patients with CHF from 1999 to 2005 treated at the Veterans Affairs Medical Center, Memphis, Tennessee, were reviewed (n = 4,735). Odds ratios with 95% confidence intervals of having a fracture associated with spironolactone use were estimated using conditional logistic regression. We identified 167 cases with a single-incident fracture and matched these by age and race to 668 control subjects without fractures. After adjustment for covariates, spironolactone use was inversely associated with total fracture (odds ratio: 0.575; 95% confidence interval: 0.346 to 0.955, p = 0.0324). The use of spironolactone is inversely associated with fractures in men with CHF.